Time-frequency and time-frequency-rate representations using the cross quadratic spectrum - Saman S Abeysekera (2013)
Traditionally used time-frequency distributions such as the STFT and the WVD are not suitable for FM signal characterization at low SNRs. A new method is proposed using the cross quadratic spectrum (XQS) which provides accurate temporal characterization for both signal's instantaneous frequency and the instantaneous-frequency-rate.